The Effects of an Upper Secondary Education Reform on the Attainment of Immigrant Youth - Christian N. Brinch; Bernt Bratsberg; Oddbjørn Raaum (Statistics Norway, Research Department, 2008)
The national Norwegian school reform of 1994, which gave statutory right to at least three years of upper secondary education, had a significant impact on educational attainment among immigrant youth. In particular, we find that the immigrant transition rate from compulsory schooling to completion of the first year of upper secondary education improved from the pre- to the post-reform period. Using a sequential binomial logit framework, we present evidence that the improvement can be attributed to reductions in capacity constraints, rather than cohort heterogeneity. An important implication is that non-targeted educational reforms may have large impacts on the educational attainment of disadvantaged groups in general and ethnic minority youth in particular.
Keywords: I21; 330; schooling transitions; immigrant youth; reform effects